Efficacy of WeChat-Based Digital Intervention Versus Metformin in Women With Polycystic Ovary Syndrome: Randomized Controlled Trial - Diliqingna Dilimulati; Xiaowen Shao; Lihua Wang; Meili Cai; Yuqin Zhang; Jiayi Lu; Yao Wang; Hongying Liu; Ming Kuang; Haibing Chen; Manna Zhang; Shen Qu (JMIR Publications, 2024)
BackgroundThe first-line treatment for polycystic ovary syndrome (PCOS) is lifestyle modification. However, it is currently unknown whether digital medicine can assist patients with PCOS in maintaining a healthy lifestyle while alleviating PCOS symptoms. ObjectiveThis study aims to evaluate the efficacy of WeChat-based digital intervention versus metformin treatment in women with PCOS and insulin resistance. MethodsA total of 80 women with PCOS and insulin resistance were recruited from an endocrinology clinic and randomly assigned to receive either a WeChat-based digital intervention (n=40, 50%) or metformin (n=40, 50%) for 12 weeks. The WeChat-based digital intervention consisted of 3 modules; a coach assisted the patients in using the intervention. The primary outcome was the change in a homeostatic model assessment for insulin resistance. At baseline and after the 12-week intervention, anthropometric parameters, menstruation frequency, sex hormone levels, metabolic factors, and body fat distribution were measured in the clinic. Furthermore, self-assessed web-based questionnaires on diet, exercise, sleep, anxiety, and depression were obtained. ResultsA total of 72 participants completed the follow-up (for a 90% follow-up rate), including 35 of 40 (88%) participants from the digital intervention group and 37 of 40 (93%) participants from the metformin group. The homeostatic model assessment for insulin resistance in the digital intervention group was significantly improved after 12 weeks of treatment with a mean change of -0.93 (95% CI -1.64 to -0.23), but no statistical difference was observed between the groups (least squares mean difference -0.20; 95% CI -0.98 to 0.58; P=.62). Both digital intervention and metformin treatment significantly improved menstruation frequency (digital intervention: P<.001; metformin: P<.001) and reduced body weight (digital intervention: P<.001; metformin: P<.001) and total fat mass (digital intervention: P<.001; metformin: P<.001). Furthermore, the digital intervention had a significant advantage over metformin in improving waist circumference (least squares mean difference -1.84; 95% CI -3.44 to -0.24; P=.03), waist-to-hip ratio (least squares mean difference -0.02; 95% CI -0.03 to 0.00; P=.03), total fat mass (least squares mean difference -1.59; 95% CI -2.88 to -0.30; P=.02), and dehydroepiandrosterone sulfate (least squares mean difference -69.73; 95% CI -129.70 to -9.75; P=.02). In terms of safety, the main adverse events were sensations of hunger in the digital intervention group (2/40, 5%) and gastrointestinal adverse events in the metformin group (12/40, 30%). ConclusionsOur data suggest that digital intervention is an effective treatment option for patients with PCOS, with an efficacy comparable to that of metformin, and that it can also alleviate the negative effects of medications and make it easier and more efficient to adhere to lifestyle treatments. WeChat-based digital interventions have the potential to provide a new path for the improvement and health of women with PCOS in China. Trial RegistrationClinicalTrials.gov NCT05386706; https://clinicaltrials.gov/study/NCT05386706